2018
DOI: 10.4038/cbj.v9i2.34
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Service Package Offered on Student Involvement: Case of Distance Education in Sri Lanka

Abstract: Despite its effectiveness, a higher student drop-out rate and lower student academic excellence are perceived as critical issues in the Distance Education (DE) system. Previous studies have emphasised on diverting attention towards core and peripheral services offered by DE institutes as a contextual solution. However, overcoming these issues only via the services offered is questionable as Students Involvement (SI) has been identified as a success factor in DE. Therefore, this paper investigates the impact co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…The proposed direct impact of peripheral services on student involvement on the basis of theory of student involvement as well as empirical findings was substantiated in the Sri Lankan context. This aligns to previous findings as they highlight that effective peripheral services encourage students to pay more attention on their academic activities (Dassanayake and Nishantha, 2017;Astin, 1984;Foubert and Grainger, 2006;Huang and Chang, 2004). Properly designed orientation programs which enable students to have an overall understanding on the DE system and means of succeeding; administrative support as dissemination of timely information, well-organized documentation processes, quick response and helpful non-academic staff members; financial support specially payment in installments, scholarships and multiple payment methods; counseling services and psychological support as well as career guidance since majority are working students who need to balance their family life and work life while learning will create a hassle-free learning opportunities and environments to students.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The proposed direct impact of peripheral services on student involvement on the basis of theory of student involvement as well as empirical findings was substantiated in the Sri Lankan context. This aligns to previous findings as they highlight that effective peripheral services encourage students to pay more attention on their academic activities (Dassanayake and Nishantha, 2017;Astin, 1984;Foubert and Grainger, 2006;Huang and Chang, 2004). Properly designed orientation programs which enable students to have an overall understanding on the DE system and means of succeeding; administrative support as dissemination of timely information, well-organized documentation processes, quick response and helpful non-academic staff members; financial support specially payment in installments, scholarships and multiple payment methods; counseling services and psychological support as well as career guidance since majority are working students who need to balance their family life and work life while learning will create a hassle-free learning opportunities and environments to students.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it can identify that core and peripheral services offered are included in and also influenced by these educational policies and practices of the institute. Since there are limited amount of previous studies that have explicitly identified the impact of these peripheral services on student involvement (Dassanayake and Nishantha, 2017), by analyzing scattered findings, it can identify that peripheral services result in effective student involvement. For instance, facilitating services as administrative support and provision of timely information address alienation feature unique to DE whereas enhancing services as multiple and flexible payment methods aligning with modern technological innovations makes it convenient for students to execute their studies without constraints.…”
Section: Impact Of Peripheral Services On Student Involvementmentioning
confidence: 99%
See 1 more Smart Citation